DINAMIKA PEMERINTAHAN DAERAH DI INDONESIA DALAM PERSPEKTIF SEJARAH - Savitri, Miya (JURNAL KONSTITUSI, 2011)
History Governance of Area in Republic Of Indonesia more than semi century this local government agency have filled journey of nation. From time to time governance of area have experienced of its transformation. At least there are seven steps till form governance of area like this time (2009). Division of this step is relied on a period to going into effect Law it arranging local governance in general. Every period of governance of area have formation and form which different each other pursuant to specified general law through Law. Proper is also noted that by used constitution also partake to influence pattern of Law arranging governance of area.Â